Parenting Guides Penggunaan Media Sosial Pada Remaja Di Lingkungan 1 Kecamatan Medan Perjuangan - R Rismayanti; Sumi Khairani; Ummul Khair; S Suriati (Jurnal TUNAS, 2021)
Social media (social media) is a medium that is not strange for the public, especially for teenagers. By using social media, teenagers can interact widely using the internet and web technology. It is undeniable that the use of social media brings so many conveniences for its users. With all the facilities provided by social media, it makes easier for users to carry out all activities such as; studying, playing games, doing business and interacting widely socially. Various access to information and entertainment from various corners of the world can be easily accessed through social media. But behind this convenience, the presence of social media also brings a bad side for its users. The most obvious and damaging impact is that teenagers can easily access immoral and violent content that is immoral. Therefore, this community service activity aims to guide and direct teenagers in using social media properly and correctly.